Bringing the individual back in: Private entrepreneurs as actors in international relations - the case of Mark Zuckerberg - Samah Abdelsabour Abdelhaey (Review of Economics and Political Science (REPS), 2019)
Purpose - This paper aims to study individuals in international relations especially private individuals in global politics. Therefore the paper focuses on analyzing the case of Mark Zuckerberg the founder and chief executive of Facebook who affects the international arena. The paper illustrates Zuckerberg's strategies to assert wide influence and power within Facebook's network and through multiple networks. Design/methodology/approach - The paper follows new theories of studying the human agent in international relations, concentrating on private individuals as new actors in international relations (IR). Thus, depending on "network making power theory" and the "three-dimensional power perspectives; (discursive, structural and instrumental)", the paper illustrates the case of Mark Zuckerberg as a private entrepreneur and his authority in the era of social media dominance with a focus on: Zuckerberg's discursive/ideational power strategy. Zuckerberg's strategy to work as a switcher through multiple networks. The most obvious one is the Facebook network, through which he can assert global influence. Findings - Formal state officials are not the only type of individuals who can affect international relations. Technological evolution has empowered private individuals as influential actors in international relations (IR). Interdisciplinary approaches became essential tools in studying new actors affecting IR. There are new patterns of power linked to individuals without formal positions. Zuckerberg, CEO of Facebook and global philanthropist, is considered an influential actor in IR depending on programming and switching strategies to assert his power in a networked world. Originality/value - This paper is able to prove that there are new forms of power which belong to private individuals in a networked world.
Keywords: 330; Bottom-up approach; Mark Zuckerberg; Network programmer; Networks switcher